(untitled) (Bulletin KNOB, 2025)
This article discusses the use of tuff stone in the period around 1000-1250 in what is now the Netherlands. During the Middle Ages tuff was used from the Rhineland to Denmark. The historiography of this subject comprises a great many books and articles on tuff and the earliest tuff stone buildings in the Netherlands, but a lack of written sources makes it difficult to get a detailed picture of the trade in tuff and its use in construction. The dating of buildings from this period is also very challenging. This article draws on contextual information in an attempt to provide more insight into the extraction, transport and trade in tuff before the year 1250, while also discussing the principal actors and material characteristics. To understand the context of tuff in the Netherlands one must first look at its distribution in Roman times. Tuff is known to have been used in over a hundred places in the Roman context and that material was sometimes reused in the Middle Ages. Although this reuse has never been systematically investigated, it can have consequences for the dating of medieval buildings, since that dating was sometimes based in part on certain characteristics of the material (block sizes). The article then looks at medieval tuff stone quarrying near Andernach. Quarrying of the stone had resumed in the tenth century, although it is impossible to give a precise date. Buyers played a crucial role, in particular the Cologne archbishops. The article names a number of these bishops as possible initiators of the interregional tuff-stone trade from the eleventh century onwards. In the Netherlands it can be assumed that the church building campaign of the Utrecht bishop Bernold had a major impact on the import of tuff from the Eifel region, judging by the massive size and regularity of the tuff-stone blocks used in the churches he commissioned. Unfortunately, building-historical aspects like masonry composition and stone sizes offer few reliable indicators for accurate dating per whole, half or quarter century. Contrary to what some writers have suggested, large- and small-sized blocks were used interchangeably. The same applies to architecture. Features like spaarbogen (arches formed in the ground to save on building material), arch friezes and other architectural-historical characteristics were used over a longer time span, some as late as the thirteenth century by which time brick had become the main building material. So the architecture of the buildings discussed here does not furnish any hard evidence for dating either. The article provides an inventory of over 500 locations where tuff was used in the Middle Ages, augmented with some 250 examples of tuff stone use in the Rhineland, thereby shedding light on the associated tuff stone landscape between Cologne and the North Sea. It concludes with an appeal for further research into each object, including systematic investigation of evidence of primary or reused (Roman) material. It is also recommended that traces of finishing be documented and mortar research be conducted, with the aim of gaining more knowledge about the Netherlands’ earliest tuff stone buildings.